Jenis Imbuhan Bagi Bahasa Melanau Mukah Berdasarkan Teori Tatabahasa Struktural Nida(1949) - Dayang Syahirah, Abang Supian (Universiti Malaysia Sarawak, (UNIMAS), 2025)
This study aims to identify the types of affixes that form derived words in the Melanau Mukah Language (BMM) based on general concepts and to describe each identified affix type using Nida’s Structural Grammar Theory (1949). The study adopts a qualitative approach and applies the theory to analyze the findings descriptively. Data were obtained from primary sources such as the Melanau Mukah – Malay Dictionary (KMMMD) (2011), which contains 8,000 entries, to gather data for both research objectives. Based on the first objective, two types of affixes were identified in BMM according to KMMMD: prefixes and infixes. The prefixes consist of five forms:/pe-/, /me-/, /ne-/, /tah-/, and /kena-/, while the infixes in BMM include three forms: /-i-/, /-u-/, and /-en-/. Each derived word found is described based on the affix pattern form, whether it involves consonant or vowel combinations. The second objective focuses on analyzing the identified affix types based on Nida’s Structural Grammar Theory (1949). This study contributes to the documentation of the Melanau Mukah language and serves as a foundation for local comparative linguistic research.